The effect of Islamic family education on early childhood prophetic character - Syahdara Anisa Makruf; Intan Puspitasari (JECCE (Journal of Early Childhood Care and Education), 2021)
Islamic education in the family is an effort to form a professional personality. Nasyiatul Aisyiyah (Nasyiah) family was chosen to be the research subject because it has a mission to strengthen family resilience. For Nasyiah, family resilience is the main foundation to form the prophetic character of Early Childhood. The purpose of the study is to analyze the effect of the implementation of Islamic education in the family on the prophetic character of early childhood. This research method uses quantitative research. The data collection process used a google form questionnaire addressed to Nasyiatul Aisyiyah cadres in the Special Region of Yogyakarta (DIY) with a total of 113 subjects. The data were analyzed using SPSS 26 and used simple linear regression. The results of this study indicate that the implementation of Islamic education has a positive effect on prophetic characters with a total effect of 42.1%. The novelty of the research lies in the prophetic character of children which has never been discussed before in the early childhood care process in the Nasyiatul Aisyiyah environment. This study provides literacy to the community that increasing the implementation of Islamic education in the family will affect the improvement of prophetic character in early childhood. Early childhood who already have a prophetic character will improve leadership in the future.